Oxygen mobility in SmBa2Cu3O7-delta measured by anelastic spectroscopy - do Nascimento, R. M.; Gimenez, J. M. A.; Grandini, Carlos Roberto [UNESP]; Cunha, A. G. (Elsevier B.V., 2006)
Anelastic spectroscopy has been performed on a sample of superconducting oxide SmBa2Cu3O7-delta (SBCO) using a torsion pendulum operating with frequency around 10 Hz. A thermally activated relaxation peak is observed near 500 K with the activation enthalpy of 1.55 +/- 0.03 eV and the pre-exponential factor of approximately 10(-15) s, which is attributed to the mobility of non-stoichiometric oxygen by jumps in positions O1 and O5 of the lattice. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: anelasticity; SBCO oxides; non-stoichiometric oxygen; internal friction